2017
DOI: 10.1080/14992027.2017.1346307
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing speech perception in noise for 5-year-old children using hearing aids or cochlear implants

Abstract: Speech perception in children with hearing loss can be enhanced by improving their language abilities. Early age at cochlear implantation was also associated with better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 58 publications
(102 reference statements)
3
49
1
1
Order By: Relevance
“…Most academic and extracurricular settings are characterized by background noise, which negatively affects speech recognition and academic outcomes in children with normal hearing (CNH), and has even greater consequences for CHH. Even though CHH have documented weaknesses with listening in noise (Crandell, 1993; Uhler et al, 2011; Caldwell and Nittrouer, 2013; Leibold et al, 2013; McCreery et al, 2015; Klein et al, 2017; Ching et al, 2018), there is little research on how their ability to recognize speech in noise develops over time during the school-age years. Increased knowledge in this area impacts both clinical decision-making and theoretical understanding of the mechanisms that drive listening in noise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most academic and extracurricular settings are characterized by background noise, which negatively affects speech recognition and academic outcomes in children with normal hearing (CNH), and has even greater consequences for CHH. Even though CHH have documented weaknesses with listening in noise (Crandell, 1993; Uhler et al, 2011; Caldwell and Nittrouer, 2013; Leibold et al, 2013; McCreery et al, 2015; Klein et al, 2017; Ching et al, 2018), there is little research on how their ability to recognize speech in noise develops over time during the school-age years. Increased knowledge in this area impacts both clinical decision-making and theoretical understanding of the mechanisms that drive listening in noise.…”
Section: Introductionmentioning
confidence: 99%
“…Stronger language skills allow individuals to make better predictions about an incoming message, even in the presence of limited sensory input (Nittrouer et al, 2013). Vocabulary knowledge accounts for a significant proportion of variance in word and sentence recognition in quiet for children with CIs and/or HAs (Blamey et al, 2001; Caldwell and Nittrouer, 2013), and language skills are significant predictors of speech recognition in noise for school-age CHH (McCreery et al, 2015; Klein et al, 2017; Ching et al, 2018). None of these studies included longitudinal data, so it was not possible to determine how these underlying mechanisms influence developmental trajectories of speech recognition in noise.…”
Section: Introductionmentioning
confidence: 99%
“…Speech perception tests for children with CIs are traditionally performed with live or recorded real words or sentences in quiet or in noise (e.g., Harrison et al, 2005; Zeitler et al, 2012; Ching et al, 2018). Such tests indisputably measure the children’s language skills in addition to their auditory skills.…”
Section: Introductionmentioning
confidence: 99%
“…Future investigations on predictors of language outcomes of children using hearing aids at 9 years will need to include a wider range of factors reported in the literature (e.g., Tomblin et al, 2015) than was used in this study. For example, we did not include hearing device use or aided audibility in this study partly because the current focus is on the role of early cognitive factors on later language development; and partly because our earlier reports on the LOCHI cohort at 3 and 5 years of age showed that these factors did not account for unique variance after allowing for the effects of a range of child- and family-related factors (Ching et al, 2013, 2018a,b). Even though the question of the link between cognitive abilities and language development is not new, the current study is the first to investigate this relationship in a prospective study of a population-based cohort of children with mild to severe hearing loss using hearing aids.…”
Section: Discussionmentioning
confidence: 99%